PERAN KEPERCAYAAN DALAM MEMEDIASI PENGARUH PERSEPSI RISIKO TERHADAP NIAT BELI ULANG PADA MARKETPLACE SHOPEE - Rianty, Dewa Ayu Osa; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023, 2023)
This study aims to analyze the role of trust in mediating the effect of perceived risk on repurchase intention. This research was conducted on marketplace Shopee in Denpasar City. This study used a sample of 120 respondents, with a non-probability sampling method. Data collection was obtained from the results of distributing questionnaires online. The analytical technique used is path analysis. Based on the response from the respondent, the results showed that all hypotheses accepted. The results indicate perceived risk has  negative and significant effect on repurchase intention. Perceived risk has a negative and significant effect to trust. trust has a positive and significant effect on repurchase intention. trust able to mediating the effect of perceived risk on repurchase intention